Validation of multiplex serology detecting human herpesviruses 1-5 - Brenner, Nicole; Pawlita, Michael (PLOS ONE, 2018)
Human herpesviruses (HHV) cause a variety of clinically relevant conditions upon primary infection of typically young and immunocompetent hosts. Both primary infection and reactivation after latency can lead to more severe disease, such as encephalitis, congenital defects and cancer. Infections with HHV are also associated with cardiovascular and neurodegenerative disease. However, most of the associations are based on retrospective case-control analyses and well-powered prospective cohort studies are needed for assessing temporality and causality. To enable comprehensive investigations of HHV-related disease etiology in large prospective population-based cohort studies, we developed HHV Multiplex Serology. This methodology represents a low-cost, high-throughput technology that allows simultaneous measurement of specific antibodies against five HHV species: Herpes simplex viruses 1 and 2, Varicella zoster virus, Epstein-Barr virus, and Cytomegalovirus. The newly developed HHV species-specific (‘Monoplex’) assays were validated against established gold-standard reference assays. The specificity and sensitivity of the HHV species-specific Monoplex Serology assays ranged from 92.3% to 100.0% (median 97.4%) and 91.8% to 98.7% (median 96.6%), respectively. Concordance with reference assays was very high with kappa values ranging from 0.86 to 0.96 (median kappa 0.93). Multiplexing the Monoplex Serology assays resulted in no loss of performance and allows simultaneous detection of antibodies against the 5 HHV species in a high-throughput manner.